THE BEGINNING OF ISLAMIC MONTHS DETERMINATION IN INDONESIA AND MALAYSIA: Procedure and Social Condition - Wahidi, Ahmad; Yasin, Noer; Kadarisman, Ali (ULUL ALBAB Jurnal Studi Islam, 2019)
Determination procedure of the beginning of Islamic months in Indonesia is done through isbat convened by Ministry of Religious Affairs. The result is considered as the official decision of government. In Malaysia, the determination is preceded by the execution of ru’yah set by the officials of Keeper of the Rulers’ Seal. The falak data are prepared by the Falak Unit at the Department of Islamic Development, the Mufti Members of the States of Malaysia as the practitioners. The results are announced by appointed officers from Mufti and Falak experts. The effort of the Indonesian Government on the unification of beginning of Islamic months determination is by establishing the Organization of Ḥisâb Ru’yah. One of its tasks and functions is to seek the unification of the beginning of Islamic months’ determination through several programs. Whereas Malaysian Government does it by synchronizing understanding about the beginning of Islamic months’ determination and after that relying on King’s decision whether there will be strict sanction related to dissimilarity of the beginning of Islamic months’ determination.